Slovenska politična misel o narodu med obema vojnama - Prunk, Janko (Javnost (Ljubljana), 2010)
Slovene political thought between the two World Wars developed in rather close correlation with European political thought of the time, with some specific indications. In spite of entering into the Yugoslav state after the World War I, Slovene political thought and Slovene political life kept the tradition of attachment to the Central-European political thought in political ideas (liberal, Christian-socialist and social democratic) and some basic views (human rights, democracy, parliamentarism, social security, social representation). In addition, political ideas of an extreme radical labour communist left emerged, especially in the 1930s, largely through the newly established hub of the state, Belgrade. The main speciality and originality of the majority of Slovene political actors of the time relate to the national question. Even in the new Yugoslav state, the Slovene national question was not ideally solved and Slovenes were not satisfied with their position in the multinational state. Considerations and solutions of these questions were mostly recognised in strong autonomy of Slovenia within the Yugoslav federation.
Keywords: Slovenia; Slovenija; politična zgodovina; narodnostno vprašanje